STUDY OF SALIVARY PH IN PATIENTS WITH THE PREVALENCE OF PERIODONTITIS WITH OR WITHOUT DIABETES MELLITUS - Maheswari tn, uma; P, sri Neeraja (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To assess the relationship between salivary pH and periodontitis in subjects with and without diabetes mellitus. The relationship between diabetes mellitus and salivary pH has been assessed. The relationship between periodontitis and salivary pH has been assessed.But the relationship between diabetes mellitus, periodontitis and salivary pH among adults has received less attention. Methods: A total of sixty subjects were evaluated in the study with no history of diabetes mellitus and periodontitis, with periodontitis but no history of diabetes mellitus, with periodontitis and diabetes mellitusas twenty in each group.pH strips were used to measure the salivary pH. Results: The results show that a decreased salivary pHwas seen in subjects having periodontitis with diabetes as compared to subjects having periodontitis without diabetes. Conclusion: Thus diabetes mellitus have a direct effect on salivary pH, reducing it from normal levels. Keywords: Periodontitis, Diabetes mellitus, Salivary pH.